ANALISIS DISTRIBUSI SPASIAL MARGA CURCUMA DIJAWA - Roemantyo Roemantyo (BERITA BIOLOGI, 2000)
Based on the distribution data of 13 species of Curcuma found in Java,spatial analyses using land status and land used thematic maps has been earned out.The purpose of this analysis is to detenvine thehabittat that usually Curcuma grows both cultivated or wild.Cluster analysis based on distance Eucledian using Statistical Program for Social Sciences(SPSS) for Window Release 6 software was administered to classify the relation between Curcuma species and their habitat.The result showed that Curcuma domestica; C. aurantiaca, C. aeruginosa, C. zedoaria, C. xanthorhiza and C.viridifolia are wide distributed in Java, but C. mangga, C. heyneana, C. purpuracens, C. soloensis, C. euchroma, C.colorata and C. borg are strickly found in specific areas only. Eventhough C. phaeocaulis, C. sylvatica and C. ochrorhiza has been reported found in Java, that species should be monitor due to limited information of this species in Java.Spatial analyses using ArcView software showed that Curcuma found in the 13 kinds of land status and land used.Curcuma mainly occupies in the habitat that classify as a "daratan" status withlanduse status as resettlement.Beside that Curcuma are also grown in the teak forest areas, but some of them have been changed to secondary forest after the timber harvested proven by landuse thematic map.Those areas are classified as a high-risk habitat due to probability status can be changed easily.Cluster diagram analyses using land status thematic maps, showed that there are some habitat similarities among C. xanthorrhiza and C. zedoaria, and then among C. aeruginosa, C. aurantiaca, C. viridiflora and also among C. borg, C. soloensis, C. mangga, C. heyneana, C. colorata, C. euchroma and C. purpuracens. Cluster diagram analysis using land use thematic showed that maps some similarities habitat also occurred betweenC. aurantiaca and C.aeruginosa, and then between C. zedoaria, C. xanthorhiza and C. viridifolia, and also between C. mangga, C. heyneana,C. purpuracens, C. soloensis, C. euchroma, C. colorata and C. borg.